Mattie’s ambition in Jennifer Donnely’s a Northern Light - Muhammad Safrin; Tri Pramesti (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2023)
The aim of this study is to describe Mattie's ambition, the causes, and the consequences of Mattie's ambition in Jennifer Donnelly's novel A Northern Light. In analyzing extrinsic elements, researchers used a psychological approach which included Individual Psychology by Judge and Kammeyer-Mueller and the theory of Career ambition. To complish this study, the writer uses psychological approach and The data analysis technique of this study is uses qualitative research. The results of this study indicate that ambitions consists of two, namely studying at Barnard and becoming a writer. Like Mattie who wants to studying at Barnard University. She did it because she really like literature. The causes of Mattie's ambition also consist of two, namely internal and external. The cause internal of ambition is that the social environment makes Mattie more active and involved in social activities. The causes external of ambition consist of two, namely, getting more life and not being separated from his mother's encouragement. The effects of Mattie's ambitions also consist of positives and negatives. The positive effect of ambition here is basically related to achievements such as in education, achievement in work, and also one's income. The negative effect of Mattie ambition causes she to lose feelings of empathy and allow herself to do whatever she want to achieve she goals, even if it means them have to hurt someone else.